Efikasi Berbagai Konsentrasi Ekstrak Daun Sirsak (Anona muricata) Terhadap Jentik Nyamuk Culex quinquefasciatus - Andri ruliansyah (Loka Litbang Kesehatan Pangandaran, 2009)
Abstract. Communicable disease was source from insect still excess at public until know. Between insect what became vector were mosquito, fly and cockroach. Insect was vector well growing in bad sanitation environment. Like dirty sewer or sewage was possibility to growing mosquito like source thing like culex spp. beside making disturbing and peacefully taking part becoming filariasis vector or another disease be caused infection filariasis warn to human a causing cripple to human body when the next stage of disease. Research goal is to know how far the difference multiple extract concentration soursop leaf to be larvasida in death of culex quinquefasciatus larvae. This research is using 3 treatment which is 0,2 %, 0,4 % and 0,6 % concentration. Treatment has been repeat 6 time. After getting enough da-ta, next step is statistic analysis with probit analysis test. The conclusions are the death of culex quinquefasciatus larvae causing by extract concentration soursop leaf, adding extract concentration soursop leaf have influence to the death of culex larvae. According probity analysis test is show that effective concentration to LC50 and LC95 with Confidence Limits is can be acepted is 95%, as one by one are 0,631 % and 1,571 % betwen top and below limits. The result of reseach can be hoping to be usefull for extermination of Culex quinquefascia-tus mosquito.